Et si les ethnosciences facilitaient la production de passerelles au sein du monde académique comme non-académique ? - Catherine Sabinot (Revue d'ethnoécologie)
Our current practices of ethnoecology in the Pacific have been resolutely built up on the ethnosciences born at the Muséum national d'Histoire naturelle in Paris and marked by several major figures of the discipline who have now passed away. Deployed, tested, bold, and sometimes shaken up on the coasts and on the islands of the Atlantic, Indian and Pacific oceans, the concepts and tools used by these ethnosciences have nourished our research. Ethnosciences have proven to be an essential field to understand the world and acknowledge the expertise of environmental practitioners; those who have regular, if not daily, interactions with non-humans. During my experience as a researcher on the three oceans, ethnosciences became the subject of debate with fishers and other people working on the land and sea, as well as with conservation and development stakeholders working in non-governmental organizations or public communities. Over time, the knowledge and ways of looking at the world revealed by this field of research have gradually crossed academic and non-academic boundaries and are now frequently at the heart of truly interdisciplinary research programs, and even at the heart of the new assessment reports of the IPBES, intergovernmental organization. In order to strengthen the science-policy interface in the field of biodiversity and ecosystem services for the conservation and sustainable use of biodiversity, long-term human well-being and sustainable development, IPBES, after having worked on regional assessments of biodiversity, is now engaged in the production of assessments targeting cross-cutting themes in which we will see that the ethnosciences have a major role to play.